UJARAN KEBENCIAN DI MEDIA SOSIAL MENURUT PERSPEKTIF ISLAM - Atikah Marwa; Muhammad Fadhlan (al-Afkar, Journal For Islamic Studies, 2021)
Social media is a tool of spreading news from and to the wider community. However, these technological advances have not been accompanied by a wise attitude in using them. Often founded hate speech there. This is very contradictory to Islamic teachings which encourage people to always respect each other. This study aimed to determine hate speech on social media based on Islamic perspective. Researchers used a qualitative approach with literature study. Data sources were news, articles, and all documents relevant to this topic. The method of data collection was literature research.The data analysis used is a content analysis through inductive and deductive approaches.The result of the discussion is that hate speech is speech that violates religious rules. Because hate speech can hurt other people. The kinds of hate speech according to Islam are backbiting, lying, namimah or provocation, and slander. The factors causing hate speech are internal and external factors. And the principles that must be had in order to avoid hate speech behavior are honest, fair, accurate and upright motives. The solution is the need for cooperation from all parties, open discussion on clear boundaries between hate speech and free speech, a comprehensive and intensive view of human nature.